Newspaper publicity for the public schools of the Philippines - Domingo, Virginia Cruz 1936- (s.n.], 1958)
The purpose of this study was to find out (1) the school news topics parents and school officials are most interested in, and (2) the extent to which these preferences are satisfied by present school publicity through the newspapers of nation-wide circulation.